2016
DOI: 10.1038/pj.2016.105
|View full text |Cite
|
Sign up to set email alerts
|

Alkylated oxygen-bridged V-shaped molecules: impacts of the substitution position and length of the alkyl chains on the crystal structures and fundamental properties in aggregated forms

Abstract: We have recently developed dinaphtho [2,3-b:2',3'-d]furan (DNF-V) derivatives as a new type of solution-processable organic semiconducting material with high carrier mobility and high emission efficiency in the solid state. In this article, we systematically investigate and reveal the impact of the substitution position and the length of the alkyl side chains on their physicochemical properties based on their packing structures. For both alkylated DNF-VV and DNF-VW derivatives, the solubilities and the phase-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…and -thiophene (C 10 −DNT−VW), suggested that the central bridging elements and the lateral alkyl side chains conclusively affect their molecular geometries, aggregated structures, and semiconducting properties. 6,7,21 Unlike the reported conventional chalcogen-bridged π-cores, V-shaped π-cores form unique bent molecular structures (bent angles between naphthalenes: 3.91−13.9°) in the solid state depending on the bridged elements and substituents (Figure 1c). The long linear alkyl chains could finely tune their herringbone (HB)packing motif by multipoint van der Waals interactions to eliminate displacements along molecular longitudinal axis while unsubstituted DNF−V and DNT−V show larger displacements of 0.43 and 1.20 Å, respectively (Figure 1c).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…and -thiophene (C 10 −DNT−VW), suggested that the central bridging elements and the lateral alkyl side chains conclusively affect their molecular geometries, aggregated structures, and semiconducting properties. 6,7,21 Unlike the reported conventional chalcogen-bridged π-cores, V-shaped π-cores form unique bent molecular structures (bent angles between naphthalenes: 3.91−13.9°) in the solid state depending on the bridged elements and substituents (Figure 1c). The long linear alkyl chains could finely tune their herringbone (HB)packing motif by multipoint van der Waals interactions to eliminate displacements along molecular longitudinal axis while unsubstituted DNF−V and DNT−V show larger displacements of 0.43 and 1.20 Å, respectively (Figure 1c).…”
Section: Introductionmentioning
confidence: 92%
“…Recently, we also developed conceptually new oxygen- and sulfur-bridged V-shaped binaphthalene π-electron cores (π-cores), dinaphtho­[2,3- b :2′,3′- d ]­furan (DNF–V) and -thiophene (DNT–V) (Figure a). , Both V-shaped derivatives showed (1) high chemical stability under ambient conditions due to deep HOMO levels of <−5.0 eV to resist oxidation by ambient O 2 , (2) suitable solubility in common organic solvents owing to their intramolecular dipole moments (Figure b), (3) high thermal stability without any reactive chemical bonds, and (4) charge carrier mobility equal or superior to currently used amorphous silicon semiconductors (0.5–1.0 cm 2 V –1 s –1 ). Comprehensive studies of their decyl-substituted derivatives, 3,9-didecyldinaphtho­[2,3- b :2′,3′- d ]­furan (C 10 –DNF–VW) and -thiophene (C 10 –DNT–VW), suggested that the central bridging elements and the lateral alkyl side chains conclusively affect their molecular geometries, aggregated structures, and semiconducting properties. ,, Unlike the reported conventional chalcogen-bridged π-cores, V-shaped π-cores form unique bent molecular structures (bent angles between naphthalenes: 3.91–13.9°) in the solid state depending on the bridged elements and substituents (Figure c). The long linear alkyl chains could finely tune their herringbone (HB)-packing motif by multipoint van der Waals interactions to eliminate displacements along molecular longitudinal axis while unsubstituted DNF–V and DNT–V show larger displacements of 0.43 and 1.20 Å, respectively (Figure c).…”
Section: Introductionmentioning
confidence: 99%